Governing Attention: On Ethical-Political Effects of Psychological Testing - Pessoa Pimentel, César; do Amaran Gama Santos, Marcus Vinícius (Revista de Psicología Universidad de Antioquia, 2022)
This paper aims, as a reflection study, to investigate some processes associated with the modulation of the perception of the subjects of contemporary societies through a historical exam of the emergence and use of tests of concentrated attention, mainly the Toulouse-Piéron tests. For this purpose, Michel Foucault’s and Nikolas Rose’s concept of governmentality and Bruno Latour’s concept of immutable-mobiles are taken as instruments of analysis. Changes in the regimes of attention are analyzed through the narratives of: Kurt Danziger about the constitution of the concept of intelligence; Jonathan Crary about the crisis of the modern individual’s capacity for perceptual synthesis; and Lev Manovich about the constitution of the body as an information domain in contemporary societies. Applying this theoretical set to the field of psychological testing, we clarify the emergence of attention tests in France, focusing on Toulouse’s notion of “biocracy”. Then, we examine contemporary PhD. theses, dissertations and articles about the test, tracking displacements in its use, involving age group, neuroscientific correlates and motivation for its use. We conclude that these displacements point to the emergence of ways of modulating attention in accordance with the demands of efficiency and initiative prominent in contemporary societies.